Convex programming approach to the shopping mall (AVM) site selection problem and Sakarya - (:unkn) unknown (My University, 2010)
The facility location is the one of the most difficult activities for the administrator as decision-makers. Decision-makers have to evaluate many alternatives for assuming all criterions to define the best location. At the present day, rapid changes have been increased uncertainties' that enterprises face with, lead into management wilderness and made difficult to decision making. In this study, convex programming, a special case of nonlinear programming problems, is used for solving the shopping center location problems in Adapazari{dotless} City Center, Sakarya.
Keywords: Convex programming; Facility location; Nonlinear programming; Shopping center